Uncertainty, Risk Taking and Marital Happiness - Anderson-Jones, William (2009)
Abstract: By analysing the effect of internal and external risks on marital happiness this paper concludes that social welfare is maximised by employment status and limiting the negative effect of children. Muslim, Christian and Sikh marriages were predominantly found to be unhappier as a parent in the household specialised in domestic labour and didn’t enter the workforce. ‘Non-religious’ groups have higher levels of female employment and consequently happier marriages. The discussion suggests that social welfare would benefit by encouraging mothers to utilise day care centres and enter the labour force immediately after their statutory maternity leave. The null hypothesis stating that only macroeconomic uncertainty influences marital happiness is comprehensively rejected.